2015
DOI: 10.3389/fncel.2015.00234
|View full text |Cite
|
Sign up to set email alerts
|

In vivo synaptic transmission and morphology in mouse models of Tuberous sclerosis, Fragile X syndrome, Neurofibromatosis type 1, and Costello syndrome

Abstract: Defects in the rat sarcoma viral oncogene homolog (Ras)/extracellular-signal-regulated kinase and the phosphatidylinositol 3-kinase-mammalian target of rapamycin (mTOR) signaling pathways are responsible for several neurodevelopmental disorders. These disorders are an important cause for intellectual disability; additional manifestations include autism spectrum disorder, seizures, and brain malformations. Changes in synaptic function are thought to underlie the neurological conditions associated with these syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 113 publications
(182 reference statements)
3
28
0
Order By: Relevance
“…In Fmr1 knockout animals, a smaller proportion of calyxes in the MNTB display simple morphology, which is associated with synaptic depression . Additionally, in vivo juxtacellular recordings detected only minor changes in excitatory spiking activity . In vitro slice physiology on the inhibitory inputs has also revealed no significant changes in most of the parameters examined for both glycinergic and GABAergic transmission .…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 92%
See 2 more Smart Citations
“…In Fmr1 knockout animals, a smaller proportion of calyxes in the MNTB display simple morphology, which is associated with synaptic depression . Additionally, in vivo juxtacellular recordings detected only minor changes in excitatory spiking activity . In vitro slice physiology on the inhibitory inputs has also revealed no significant changes in most of the parameters examined for both glycinergic and GABAergic transmission .…”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 92%
“…These include KCa1.1 (BK), Kv4.2, and HCN channels, which shape the excitability of many types of neurons in the auditory system, but their roles in auditory processing in FXS have not been investigated. Because FXS is a neurodevelopmental disorder, it is likely that there exist compensatory mechanisms that act over time to alter the excitability and synaptic transmission in the patients and in animal models of the disease …”
Section: Fmrp Regulates the Development Of Synaptic Transmission In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In FXS, where it is thought that there is hyperexcitability of sensory systems due to imbalances in the excitation and inhibition (Rubenstein & Merzenich, ), impairments in MNTB processing may be particularly pronounced. However, recently it has been shown that despite changes in calyx morphology, there were no obvious changes in synaptic transmission in vivo in Fmr1 −/− mice (Wang, de Kok, Willemsen, Elgersma, & Borst, ). There was however a trend towards longer synaptic latencies in the Fmr1 −/− mice and this study did not specifically target the medial or lateral MNTB where we have seen (along with others, Strumbos et al, ) potential tonotopic differences in the MNTB of Fmr1 −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The homozygous Hras G12V knock-in mice generated by Schuhmacher and colleagues showed altered anxiety and mild deficits in the hidden-platform version of the Morris water maze (Viosca, Schuhmacher, Guerra, & Barco, 2009). This mutant also did not show deficits in in vivo synaptic transmission and short-term plasticity at the calyx of Held synapse (Wang, de Kok, Willemsen, Elgersma, & Borst, 2015). Testing behavioral and electrophysiological phenotypes in the other Hras G12V knock-in mutants, which showed more severe phenotypes such as development of papillomas and angiosarcomas, would be of interest (Chen et al, 2009).…”
Section: Postsynaptic Hras and Csmentioning
confidence: 96%